Polymers for energy storage and conversion - Mittal, Vikas (Hoboken, N.J. : John Wiley & Sons, Inc. ; Salem, Mass. : Scrivener Pub., 2013)
Polymers are increasingly finding applications in the areas of energy storage and conversion. A number of recent advances in the polymer molecular structure control thereby tuning of the polymer properties have led to these applications. This book assimilates these advances in the form of a comprehensive text which includes the synthesis and properties of a large number of polymer systems for applications in the areas of lithium batteries, photovoltaics, solar cells, etc. Polymers for Energy Storage and Conversion describes: PVAc-based polymer blend electrolytes for.
Includes bibliographical references and index.
Keywords: Conducting polymers; Polyelectrolytes; Electric insulators and insulation -- Polymers; Polymers; Polymers -- Electric properties; Electric batteries; SCIENCE -- Chemistry -- Physical & Theoretical; Conducting polymers; Electric batteries; Electric insulators and insulation -- Polymers; Polyelectrolytes; Polymers; Polymers -- Electric properties; Electronic books; Electronic books